"Vegie gelatin", why not?: extensive research to explore the potential of Malaysian plants - Jaswir, Irwandi (TM-Info-Media Sdn. Bhd., 2009)
Gelatin is one of the most widely used food ingredients. Its applications in food industries are very broad including enhancing the elasticity, consistency and stability of food products. Gelatin is also used as a stabilizer, particularly in dairy products and as a fat substitute that can be used to reduce the energy content of food without negative effects on the taste. Besided the food industry, gelatin is also useful in medicine, pharmaceutical and photographic industries.